Indigenous land rights and dynamics of the land market in Kuala Lumpur, Malaysia - Omar, Ismail; Md Yusof, Aminah (Pergamon Press, 2002)
This paper raises a number of important issues relating to legal and economic development concepts. It concentrates on the supply constraints affecting land development decisions of both private and public landowners in releasing land for development purposes. With reference to the indigenous land rights in Kuala Lumpur, this paper focuses on the restrictions in interest, which may limit the land from being transferred in the open market. With a limited market, the indigenous land achieves a lower value in the market place because transactions are limited within a particular group of people only. As a result, the market forces are restricted and the land development process for urban regeneration often comes to a halt. In examining the role of the indigenous land market in the redevelopment process of Kuala Lumpur, the study uses an institutional analysis to show the way in which these restrictions in interest affect landowners’ decisions and, thus, restrict the supply of land to real estate redevelopment. In conclusion, the paper shows various causes for land supply constraints and ways to improve these with the aim to undertake urban redevelopment initiatives considering pressure for more land in the market.